EFEK ULCEROGENIC DISPERSI PADAT IBUPROFEN-POLIVINILPIROLIDON (PVP) PADA TIKUS PUTIH JANTAN - Febrianti, Ririt Vita; Wahyuningsih, Iis (Universitas Ahmad Dahlan, 2013)
Ibuprofen is an anti inflammatory, analgesic, and antipyretic agent. It has low solubility and bioavailability.The administration of ibuprofen in a long time and high dose can increased of side effect at gastrointestinal (pepticulcer). This study was aimed to determine the influence its solid dispersions formation on ulcerogenic effect ofibuprofen buprofenis compared with ibuprofen alone and physical mixture. Solid dispersion of Ibuprofen-PVP(1:1) was prepared by solvent method. The ulcerogenic test was conducted by observing is white rat, dividedrandomly into 5 groups are healthy group (aquadest), suspending agent control (PVP 1%), drug (ibuprofen) at adose of 360 mg/kg body weight, group solid dispersion (ibuprofen-PVP) and group physical mixture(ibuprofen-PVP). Rats gastric was observed of formation ulcer and evaluated by scoring then followed thecalculation by the index ulcer. The results showed that the number of ulcer index of ibuprofen is 6,67. Number ofulcer index of solid dispersion was 4,00 and physical mixture was 3,34. The ulcerogenic effect of solid dispersionand physical mixture difference was significant (p<0,05) compared with ibuprofen alone. Ulcerogenic effectadministration of solid dispersion was smaller than ibuprofen alone and statistically no different (p>0,05)compared with physical mixture.